دراسة حركية الإصابة بالديدان Dactylogyrus)) المتطفلة على أسماك الكارب في مزرعة السن. (Latakia University Journal -Basic Sciences Series, 2018)
لقد درست ديدان الجنس (D.) Dactylogyrus (وحيدات الجيل Monogenea) الطفيلية على 440 سمكة كارب عادي، بأعمار من 40 يوم حتى سنتين، أخذت العينات عشوائياً بفاصل زمني لا يقل عن 15 يوم من مزرعة السن خلال الفترة ما بين 4/10/2000-2/10/2001. تم عزل و تصنيف أربعة أنواع طفيلية تتبع للجنس (D.) توضعت على الغلاصم وهي: D.minutus D.arquatus ,D.anchoratus, D.extensus, اختلفت هذه الأنواع في نسب إصابتها (خمجها) للأسماك حيث بلغت نسبة الإصابة  بديدان(D.) %89.1  و كان النوع D.minutus الأكثر إنتشارا حيث حقق نسبة إصابة وصلت إلى  %85.23  وقد أبدت معظم هذه الطفيليات علاقة مباشرة ببعض المؤشرات البيئية خصوصا الحرارة و اختلافاتها خلال أشهر السنة. صنفت هذه الأنواع الطفيلية لأول مرة في مياه الساحل السوري العذبة بينما صنف النوع D.arquatus لأول مرة في سوريا. This study was performed on parasitic worms of the  species Dactylogyrus (D.) (monogenea) in 440 fish individuals of the common carp (Cyprinus carpio) from Al Sin fish farm, of the age 40 days till two years old.  The samples were collected randomly at time intervals of at least 15 days throughout the period from 4-10-2000 till 2-10-2001. Isolation and classification were performed for four gill parasitic worm species of the type  D.: (D.minutus –D. arquatus. –D. anchoratus- D.extensus).  These species varied in the rate of their infection.     The rate of infection in the worm type (D) was 89.1% and the type D. minutus was the most widely prevalent to reach the infection rate of 85.23%. Most of these parasitic worms have proved to have direct relationship with some environmental factor, particularly temperature which varies throughout the months of the year. These parasitic species were recorded for the first time in the fresh waters of the coastal region.  The species D. arquatus was classified for the first time in Syria.